Gold nanorods modified Eu: Y2O3 dispersed PVA film as a highly sensitive plasmon-enhanced luminescence probe for excellent and fast non-enzymatic detection of H2O2 and glucose - Kumar D.; Dwivedi A.; Srivastava M.; Srivastava A.; Srivastava A.; Srivastava S.K. (My University, 2025)
This article addresses a high sensitivity, non-invasive, and use-throw in nature type biocompatible Eu: Y2O3 dispersed PVA film with gold nanorod (AEYCP film) fluorescent sensing probe for non-enzymatic detection of hydrogen peroxide (H2O2) and glucose (C6H12O6). The fluorescence spectra of the as-synthesized AEYCP fluorescent film consist of some sharp emission (most intense peak at ∼611 nm, owing to the 5D0-7F2 transition) which corresponds to electrical and magnetic dipole transitions. In the presence of H2O2 and glucose, the fluorescence intensity of the AEYCP film gets quenched due to the reduction of electron-hole pair, at the Eu center. The AEYCP film shows excellent fluorescence quenching in the presence of H2O2 at ∼500 nM (with a low detection limit of 1.80 × 10−9 M) and glucose (with a low detection limit 1.60 × 10-6 M). Herein, we envision that our result provides an insight for the synthesis of rare earth metal-doped oxide flexible,non-enzyme mimicking fluorescent probe for different biomedical applications. © 2020 Elsevier GmbH